ZOONOTIC POTENTIAL OF ANCYLOSTOMOSIS AND ITS PREVALENCE IN STRAY AND PET DOGS OF LAHORE METROPOLITAN - K. Ashraf; M. A. Hafeez; A. Maqbool; Z. I. Chaudhary; M. S. Khan; M. F. Rasool (Journal of Animal and Plant Sciences, 2019)
The present research was intended to appraise the prevalence rate of Ancylostomosis in dogs and its potential risk for human beings. The exploration was carried out at Lahore to define the prevalence and zoonotic potential of the Ancylostomosis. The metrological data (temperature, humidity & rain fall) was collected from the Metrology Department, Government of Pakistan, Lahore during the time of study. Out of 600 stray and pet dogs under study, 133 (22.16%) were found positive. The prevalence during the summer and winter was found 31.0 % and 15% respectively (p< 0.05). In pups prevalence was found more as compared to adult dogs. Moreover, both females (38.9%) and males’ pet owners (39.8%) seem to have an equal chance for contracting this disease. The disease was more prevalent in Nasir Bagh Park (36.9%). The prevalence of L3 larvae of A. caninum was recorded high (22-30%) during summer and rainy season in different public parks under study. The investigation clinched that high infection rate was found in the summer season succeeded by monsoon and the least in winter.
Keywords: Prevalence; Dog; Zoonosis; Ancylostomosis; Lahore